Knowledge, Attitude, and Practice Related to Antibiotic Use among Adult Population in Urban Slums of Burdwan Municipality, Purba Bardhaman District of West Bengal: A Cross-sectional Study - Sayanti Chingri; Sulagna Das; Sukanya Gupta (Acta Medica International)
Introduction: Antibiotic resistance (ABR) poses a considerable challenge to global public health. Appropriate antibiotic usage plays a pivotal role toward preventing emerging ABR. The objectives of this study were to assess the knowledge, attitude, and practice (KAP) regarding antibiotic use among the adult population (≥18 years) in urban slums of Burdwan Municipality and to find out the associations, if any, between sociodemographic characteristics and level of KAP. Materials and Methods: A descriptive, cross-sectional study was done on 270 adults residing in slums of Burdwan Municipality during September–October 2023. Subjects were selected by simple random sampling. Data were collected by interviewing the respondents using a predesigned, pretested, semi-structured schedule. Data were analyzed using descriptive statistics and Chi-square tests. Results: The mean age of participants was 38.16 (±13) years. The majority (63.7%) of them were females, 25.6% were educated up to middle school, and 41.1% were homemakers or retired persons. It was found that only 35.9% population had better knowledge, 47.8% had a positive attitude, and 48.5% of the population had an appropriate practice of antibiotics. Almost a quarter (23.70%) of the population was unaware of the term antibiotics. The Chi-square test revealed gender, occupation, and education to be significantly associated with knowledge, attitude, and practice of antibiotic usage among respondents. Conclusion: The findings underscore the importance of targeted educational interventions to improve the knowledge about antibiotics and promote rational antibiotic use among urban slum dwellers. Efforts to combat ABR must prioritize addressing KAP gaps in diverse community settings to mitigate the threat of antimicrobial resistance.